Analisis Perizinan Olah Gerak Kapal (Shifting Permit) menggunakan Sistem Operasi Layanan Kapal Digital guna mendukung Operasional Transhipment di Pt. Dian Ciptamas Agung Site Bunati - Vickri Ananda Pringgondani; Sitti Syamsiah; Nurul Hatifah (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research is motivated by the existing obstacles in processing the shifting permit activities. This study aims to analyze the management of shifting permit activities using the digital ship service operations system at PT. Dian Ciptamas Agung, Bunati Site, as well as to identify and evaluate the obstacles and efforts that can be made to support transhipment operations. This research uses a descriptive qualitative approach with data collection methods including participatory observation, interviews, and document studies. The research is conducted at PT. Dian Ciptamas Agung, Bunati site, South Kalimantan Province. The implementation of this research will take place over approximately 12 months ( August 4, 2024 – July 15, 2025). The process of obtaining a shifting permit for transhipment operations at PT. Dian Ciptamas Agung, Bunati Site has referred to and complied with Law Number 66 of 2024 and Minister of Transportation Regulation Number PM 8 of 2022. This is supported by the existence of digital vessel service operating systems such as Inaportner and Phinnisi. Nonetheless, several obstacles are still encountered, such as the submission of the Letter of Application for Ship Movement (SPOG) being delayed due to the mooring PPK not appearing automatically on Inaportnet, and the submission for pilotage requests on the Phinnisi system being rejected due to the Pelindo operator entering the wrong time in the Vessel Berthing Plan (RPK).